Formula dan Manfaat Daun Mindi (Melia Azedarach L) sebagai Antidiabetes: Tinjauan Pustaka - Noviana, Ineke; Gunawan, Yosephina E S; Toru, Veronika; Wahyudi; Sukartiningsih, Maria Ch. Endang (JURNAL KESEHATAN PRIMER, 2023)
Background: The International Diabetes Federation (IDF) estimates that there will be an increase in the number of people with DM in Indonesia from 9.1 million in 2014 to 14.1 million in 2035. With this figure, Indonesia is ranked 5th in the world. According to the 2013 Basic Health Research, the proportion of DM was 6.9% and was 10.9% in 2018. The increasing DM population has resulted in various complications including retinopathy, neuropathy and other complications. In one study it was found that diabetes patients with a history of diabetic ulcers had a 47% increased risk of death. Objective: the purpose of this literature review research is to obtain a theoretical overview of the results of other people's research that can support the solution of the problem being handled carefully. Method: A research method that searches and examines several journals or articles related to the subject of research to create a written work on a certain topic. Method: The method in this research is a literature review which contains descriptive findings from others research. Results: search for articles discussed in this research were 2 national journals and 3 international journals. In the article discussed, the results show that mindi has good antioxidant content, contains flavonoids and can reduce sugar levels. From laboratory and experimental tests, the results produced are significant in reducing sugar levels and contain flavonoids which are useful in warding off free radicals.